Plasminogen Activator Inhibitor-1 in Acute Myeloid Leukemia: Is It Useful in Predicting Response to Induction Remission Therapy? - Al-Shammari, Haider Hasan Jaleel; Al-Bayaa, Israa; Al-Rubaie, Haithem Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Coagulation and fibrinolytic abnormalities are common in patients with acute myeloblastic leukemia (AML). Plasminogen activator inhibitor (PAI) activity is believed to be elevated during the initial diagnosis and relapse of AML patients. AIM: This study aimed to evaluate the levels of plasma PAI-1 activity in AML patients before and after remission induction. METHODS: Thirty AML patients and 20 healthy volunteers were included in this study. The patients were classified according to AML-FAB subtypes. All patients received 7+3 induction chemotherapy. They were evaluated for complete remission after induction chemotherapy and followed up for 6 months. RESULTS: PAI-1 activity was measured by ELISA immunoassay. PAI-1 activity was significantly higher in AML patients than the control group (P=0.016), whereas there was insignificant difference among patients in various AML subgroups (P>0.05). Before and after treatment, there was a significant difference in PAI-1 activity between patients with active disease and those at remission (P= 0.023 and <0.0001, respectively). CONCLUSION: High PAI-1 activity in AML patients is found to be associated with poor response to treatment.